Copper-Induced Intra-Specific Oxidative Damage and Antioxidant Responses in Strains of the Brown Alga Ectocarpus Siliculosus with Different Pollution Histories - Moenne-Munoz, A (Elsevier, 2015)
Inter- and intra-specific variation in metal resistance has been observed in the ecologically and economically important marine brown macroalgae (Phaeophyceae), but the mechanisms of cellular tolerance are not well elucidated. To investigate inter-population responses of brown seaweeds to copper (Cu) pollution, the extent of oxidative damage and antioxidant responses were compared in three strains of the filamentous brown seaweed Ectocarpus siliculosus, the model organism for the algal class Phaeophyceae that diverged from other major eukaryotic groups over a billion year ago. Strains isolated from locations with different pollution histories (i.e. LIA, from a pristine site in Scotland; REP and Es524 from Cu-contaminated sites in England and Chile, respectively) were exposed to total dissolved Cu concentrations (CuT) of up to 2.4μM (equivalent to 128nM Cu2+) for 10d. LIA exhibited oxidative stress, with increases in hydrogen peroxide (H2O2) and lipid peroxidation (measured as TBARS levels), and decreased concentrations of photosynthetic pigments. Es524 presented no apparent oxidative damage whereas in REP, TBARS increased, revealing some level of oxidative damage. Adjustments to activities of enzymes and antioxidant compounds concentrations in Es524 and REP were strain and treatment dependent. Mitigation of oxidative stress in Es524 was by increased activities of superoxide dismutases (SOD) at low CuT, and catalase (CAT) and ascorbate peroxidase (APX) at all CuT, accompanied by higher levels of antioxidants (ascorbate, glutathione, phenolics) at higher CuT. In REP, only APX activity increased, as did the antioxidants. For the first time evidence is presented for distinctive oxidative stress defences under excess Cu in two populations of a species of brown seaweed from environments contaminated by Cu. © 2014.